2017
DOI: 10.4236/ijg.2017.84031
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Open Source Spatial Data for Landslide Susceptibility Mapping at Chittagong District of Bangladesh—An Appraisal for Disaster Risk Reduction and Mitigation Approach

Abstract: Since creation of spatial data is a costly and time consuming process, researchers, in this domain, in most of the cases rely on open source spatial attributes for their specific purpose. Likewise, the present research aims at mapping landslide susceptibility at the metropolitan area of Chittagong district of Bangladesh utilizing obtainable open source spatial data from various web portals. In this regard, we targeted a study region where rainfall induced landslides reportedly causes causalities as well as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The reason behind selecting the power based regressive curve is that the highest value of the coefficient R 2 was found for power curve compared to other curves like linear, logarithmic, exponential, etc. Again, Islam et al (2017) showed that all the failed slopes in the Chittagong City has slope angle (β) > 15 o . Therefore, we assumed the FS values below the crossing point of the line representing tan15 o and the best-fit curve as unsafe and the FS values above the point as safe in terms of rainfall induced landslide hazard in the study region.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason behind selecting the power based regressive curve is that the highest value of the coefficient R 2 was found for power curve compared to other curves like linear, logarithmic, exponential, etc. Again, Islam et al (2017) showed that all the failed slopes in the Chittagong City has slope angle (β) > 15 o . Therefore, we assumed the FS values below the crossing point of the line representing tan15 o and the best-fit curve as unsafe and the FS values above the point as safe in terms of rainfall induced landslide hazard in the study region.…”
Section: Methodsmentioning
confidence: 99%
“…Chittagong city, in the southeastern hilly region of Bangladesh, is a landslide prone city, where almost every year devastating landslides result in casualties and damage to properties (Islam et al, 2017, Mia et al, 2017. Table 1 represents some of the major historic and recent landslide events.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations